The burden of human African trypanosomiasis - Fèvre, Eric M.; Wissmann, B.V.; Welburn, S.C.; Lutumba, P. (Public Library of Science, 2008)
Human African trypanosomiasis (HAT, or sleeping sickness) is a protozoan parasitic infection caused by Trypanosoma brucei rhodesiense or Trypanosoma brucei gambiense. These are neglected tropical diseases, and T.b. rhodesiense HAT is a zoonosis. We review current knowledge on the burden of HAT in sub-Saharan Africa, with an emphasis on the disability-adjusted life year (DALY), data sources, and methodological issues relating to the use of this metric for assessing the burden of this disease. We highlight areas where data are lacking to properly quantify the impact of these diseases, mainly relating to quantifying under-reporting and disability associated with infection, and challenge the HAT research community to tackle the neglect in data gathering to enable better evidence-based assessments of burden using DALYs or other appropriate measures.